2020
DOI: 10.1021/acs.jafc.0c02629
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Necrotizing Enterocolitis through Milk Polar Lipids Reducing Intestinal Epithelial Apoptosis

Abstract: Neonatal necrotizing enterocolitis (NEC) is a common and devastating disease. The objective of this research was to investigate the protective mechanisms of milk polar lipids (MPLs) on the attenuation of lipopolysaccharides (LPS)-induced intestinal inflammation and apoptosis. MPLs were extracted from buttermilk and analyzed using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). A neonatal NEC rat model was used to investigate the effects of MPLs on NEC and its underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Enteral treatment with MPL, which are abundantly present in MFGM, increased intestinal IL10 protein expression, while decreasing intestinal TNFα, IL6 and IL8 protein expression and TLR4 immunoreactivity [84]. In addition, MPL inhibited NEC induced intestinal p65 and p50 expression [84]. Pomegranate seed oil, rich in unsaturated fatty acids such as conjugated linolenic acids and oleic acid, blocks an increase in ileal gene expression of IL6, IL8, IL12, interleukin 23 (IL23) and TNFα in neonatal rats during NEC [47].…”
Section: Fat-based Feeding Interventionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Enteral treatment with MPL, which are abundantly present in MFGM, increased intestinal IL10 protein expression, while decreasing intestinal TNFα, IL6 and IL8 protein expression and TLR4 immunoreactivity [84]. In addition, MPL inhibited NEC induced intestinal p65 and p50 expression [84]. Pomegranate seed oil, rich in unsaturated fatty acids such as conjugated linolenic acids and oleic acid, blocks an increase in ileal gene expression of IL6, IL8, IL12, interleukin 23 (IL23) and TNFα in neonatal rats during NEC [47].…”
Section: Fat-based Feeding Interventionsmentioning
confidence: 95%
“…Enteral supplementation of bovine MFGM reduces ileal mRNA expression of IL1β, TNFα and IL6, as well as protein expression of TLR4 [48], whereas TLR9 signaling remained unaffected [48]. Enteral treatment with MPL, which are abundantly present in MFGM, increased intestinal IL10 protein expression, while decreasing intestinal TNFα, IL6 and IL8 protein expression and TLR4 immunoreactivity [84]. In addition, MPL inhibited NEC induced intestinal p65 and p50 expression [84].…”
Section: Fat-based Feeding Interventionsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a neonatal rat model of NEC induced by hypoxia and hypothermia, formula-fed pups supplemented with bovine MFGM demonstrated increased weight gain, reductions in NEC incidence and mortality, and a decrease in intestinal damage as compared with pups fed formula alone [185]. Yang et al reported that treatment of neonatal rats with a bovine milk polar lipid extraction, including both sphingolipids and phospholipids, reduced NEC symptoms through a reduction in both apoptosis and inflammation in the intestinal epithelium [186]. Though supplementation of bovine MFGM does not address the discrepancy in MFG size between infant formula and HM, the individual protein, sphingolipid, and phospholipid components of the MFGM clearly exert positive physiological influences in the postnatal environment [22].…”
Section: Complex Lipidsmentioning
confidence: 99%
“…CLA could ameliorate DSS-induced colitis in mice model, 28 and MPLs could ameliorate necrotizing enterocolitis (NEC) in rat model by inhibiting the in ammatory response. 29 Lorea et al reported that the yogurt contained probiotics possessed anti-in ammatory effects in IBD patients. 30 These reports prompt that the B. subtilis fermented milk might be applied as a functional food for prevention and curation of IBD in the future.…”
Section: Introductionmentioning
confidence: 99%